ASSESSMENT OF NUTRITION ADVOCACY IN SOMALIA REPORT: GAPS, OPPORTUNITIES AND KEY MESSAGES - Ouma, George; Mohamed, Farah; Rithaa, Gilbert; Hassan, Mohamed (Global Journal of Health Sciences, 2021)
Purpose: This inception report on the comprehensive assessment through desk reviews and analysis nutrition gaps in policy, political commitment, resource allocation and multi-sectoral coordination to inform the development of guideline and messages. This is as a follow-up of preliminary discussion held and concept agreed with the office of the national coordination for Scaling Up Nutrition (SUN), Somalia housed in the Office of Prime Minister (OPM), Federal Government of Somalia. This summary report presents findings from the assessment and a discussion of methodology, challenges and opportunities. By identifying and contextualizing new findings, nutrition advocacy assessment builds consensus in Somalia with a vision and path ahead for improved nutrition messaging and guidelines that various actors will use of advocacy work. Methodology: 30 documents were gathered and reviewed, including - national legislation, policies, guidelines, strategies and action plans to assess the inclusion of adolescents and current gaps. Interviews were conducted with 20 stakeholders from government, donors, UN, communities and non-governmental institutions in Somalia. The review, analysis and stakeholder interviews assessed the extent to which nutritional aspects were being addressed, any gaps in the policy landscape, commitments, multi-sectoral coordination, advocacy initiatives and recommendations for strengthening the enabling environment. Findings: It was established that awareness of SUN as a movement in Somalia was rated highly at however participation in SUN activities was very low and was left to nutritionist in the various sector/Institutions. Government has also shown a great political will and commitment to nutrition by ensuring policies and legislative frameworks are sufficient even though multi-sectoral nutrition integration is not optimal to impact desired impact. Unique contribution to theory, practice and policy: It was recommended that there is need to advocate political and administrative authorities, to further convince them to add nutrition among the top priorities of the governments, translate policies into actions and ensure allocation of funds for nutrition interventions. Also, Government must strongly provide leadership in nutrition policy development, programing and coordination.